Pushing temperature boundaries in wood-plastic composites’ manufacturing by transdisciplinary paradigm shift: Novel functionalities, higher resource efficiency, and extended application range - Aleksander Hejna; Mateusz Barczewski (Journal of Bioresources and Bioproducts)
Wood-plastic composites (WPCs) combine the advantages of plastics and lumber, however, their progress is slowed by limitations resulting from the properties of plant-based materials (PBMs), the most critical of which is insufficient thermal stability. The temperature boundary for processing of WPCs is 200 °C, as higher temperatures induce PBMs’ degradation, yielding odor, uncontrolled darkening, porosity generation, and loss of WPCs’ mechanical performance. Going beyond the framework of composites’ science and taking a transdisciplinary look at processing degradation leads to very different conclusions. The food sector makes the best of PBMs’ degradation, yielding not only indispensable feed but often works of art. Drawing from its experience with the desire to go beyond the state-of-the-art, WPCs need a paradigm shift considering processing degradation. The presented paper proposes the pathway against the flow. Instead of avoiding processing degradation, deliberately inducing and employing it with all the benefits, pushing WPCs toward sustainability by maximizing resource efficiency. Exceeding the temperature limit will enable the use of engineering plastics, which outperform commodity types. Considering PBMs, it will not only unleash the true potential of phytochemicals but also take advantage of the compounds yet to be generated in situ during processing degradation, enriching WPCs with benefits known from the food sector.